Effect of whole body cryotherapy on low back pain and release of endorphins and stress hormones in patients with lumbar spine osteoarthritis - Marta Barłowska-Trybulec; Klaudia Zawojska; Joanna Szklarczyk; Marta Góralska (Rheumatology, 2022)
Introduction Low back pain (LBP) is the most common ailment in patients with lumbar spine osteoarthritis (OA). There are many methods to treat LBP, such as manual therapy, osteopathy, massage, physical exercise, and physical therapy. The most effective of these are manual therapy and exercises combined with physical procedures, such as whole body cryotherapy (WBCT). Whole body cryotherapy can induce various hormonal adaptations in patients with OA. This is probably the body’s reaction to cold and stress. The purpose of the study was to evaluate the impact of WBCT on β-endorphins, cortisol and adrenaline release, as well as on LBP in patients with OA of the lumbar spine.